Comparative Dissolution Study Between Resveratrol Nanocream Formula and Conventional Resveratrol Cream with Dimethylsulfoxide Addition - Dewi Fitriani Puspitasari; Rahmawati Salsa Dinurrosifa (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Resveratrol has potential activity as an antioxidant. Several studies have formulated resveratrol into topical preparations, but the low solubility of resveratrol causes low release of the active substance. Dimethylsulfoxide is a widely used ingredient in topical preparations, which can be used to increase the solubility of poorly soluble substances Nanocream is a nanoparticle-based topical drug delivery. The globule size is nanoscale, which can help improve drug solubility. The aim of the research was to conduct a comparative dissolution study between resveratrol nanocream formula and resveratrol conventional cream preparation with the addition of dimethylsulfoxide at various concentrations of 3%, 5% and 7%. The research method began with formulating resveratrol nanocream preparation. The preparation consisted of lipid components dispersed into a cream base. The lipids consisted of VCO, tween 80 and propylenglycol. Loading drug of resveratrol lipid was 300 mg, then tested for transimtance value and globule size. Conventional resveratrol cream formula was made into FI, FII and FIII, where each formula used different concentration of DMSO. Physical characteristics testing was conducted on nanocream and conventional resveratrol cream.Analysis of dissolution test results was observed among FI, FII and FIII in conventional cream formulas. The dissolution test results of these three formulas were also compared with the resveratrol nanocream preparation. Observation of dissolution results was assessed from the percentage of active substance released at minutes 5, 10, 15, 30, 45, 60.The dissolution test results showed that there was no significant difference in the percentage of active substance released between the conventional resveratrol cream preparation formulas, but there was a significant difference between the three conventional resveratrol cream preparation formulas and the resveratrol nanocream preparation.